Advances in Mechanism Research on Polygonatum in Prevention and Treatment of Diabetes - Liu, Shuang; Jia, Qiao-Jun; Peng, Yi-Qing; Feng, Ting-Hui; Hu, Shu-Ting; Dong, Juan-e; Liang, Zong-Suo (Frontiers in Pharmacology, 2022)
Diabetes mellitus is a fast-growing disease with a major influence on people’s quality of life. Oral hypoglycemic drugs and insulin are currently the main effective drugs in the treatment of diabetes, but chronic consumption of these drugs has certain side effects. Polysaccharides, saponins, flavonoids, and phenolics are the primary secondary metabolites isolated from the rhizomes of Polygonatum sibiricum Redouté [Asparagaceae], Polygonatum kingianum Collett & Hemsl [Asparagaceae], or Polygonatum cyrtonema Hua [Asparagaceae], which have attracted much more attention owing to their unique therapeutic role in the treatment and prevention of diabetes. However, the research on the mechanism of these three Polygonatum spp. in diabetes has not been reviewed. This review provides a summary of the research progress of three Polygonatum spp. on diabetes and its complications, reveals the potential antidiabetic mechanism of three Polygonatum spp., and discusses the effect of different processed products of three Polygonatum spp. in treating diabetes, for the sake of a thorough understanding of its effects on the prevention and treatment of diabetes and diabetes complications.